A fractional path-loss compensation based power control technique for interference mitigation in LTE-A femtocell networks - Saad, Sawsan Ali; Ismail, Mahamod; Nordin, Rosdiadee; Ahmed, Afaz Uddin (Physical communication, 2016)
Introduction of Femtocells in heterogeneous network enhances the capacity, indoor coverage of the existing macrocell based network. It also allows high-speed data services for the multi-media application and software. However, in dense co-channel deployment scenarios femtocells cause severe interference to the neighbouring cells users. In this paper, a downlink-power-control scheme is presented for femtocell with no overhead signalling exchange with the macrocell. The femtocell adjusts the transmit power subject to home user equipment (HUE) measurements. The minimum level of transmit power is determined by the target Signal to Interference and Noise Ratio (SINR) of femtocell user that is set according to the required Quality of Service (QoS) of the femtocell users. The system level simulations confirm that, the proposed scheme reduces the outage probability of the nearby macrocell user equipment (MUE) up to 16.7% compared to fixed power setting, while maintaining the spectral efficiency of femtocell users. Furthermore, the transmit power can be reduced by 52.6% which leads to power effective solution of the interference scenario.